736 Update in exploring the connection and clinical implications between vitamin D and knee osteoarthritis (Balneo and PRM Research Journal, 2024)
Knee osteoarthritis is a prevalent joint disorder characterized by cartilage degeneration, pain, and impaired physical function. Vitamin D might be implicated in the management of knee osteoarthritis through its effects on bone health, cartilage preservation, inflammation modulation, and muscle function. This literature review aims to synthesize the current state of literature to provide information about the correlation between vitamin D and knee osteoarthritis. Methods: We conducted a comprehensive literature search in databases such as PubMed, Web of Science, Scopus, and Google Scholar to identify studies published in the last ten years investigating the association between vitamin D and knee osteoarthritis. Vitamin D deficiency has been linked to cartilage degeneration and more severe symptomatology of knee osteoarthritis. The evidence supports an association between vitamin D levels and knee osteoarthritis, but with some studies showing mixed results, there is a need for further research.